Role of polyglutamylation in nucleosome assembly protein 1 (NAP1) function - Subramanian, Vidya, author; Luger, Karolin, advisor (Colorado State University. Libraries, 2008)
The organization of DNA into chromatin requires the systematic deposition of the histones onto the DNA template. Chromatin function requires the dynamic exchange of the histone components during replication and transcription. Deposition and exchange is mediated in part by a family of proteins generally referred to as histone chaperones. It has been shown recently that recombinant yeast NAP1 (yNAP1) is capable of promoting ATP-independent histone exchange and nucleosome sliding in vitro, and this ability is specifically attributed to the highly acidic C terminal tail of the protein. Drosophila NAP1 (dNAP1) has a shorter acidic C terminus than yNAP1. Preliminary data in the lab suggests that recombinant wild-type dNAP1 is incapable of this nucleosome dissociation. Native dNAP1 purified from Drosophila embryos, on the other hand, is capable of nucleosome dissociation. In this study we reveal the presence of a unique post-translational modification, polyglutamylation in native dNAP1, which restores the nucleosome dissociation function to recombinant dNAP1. We have also been able to identify two target sequences, as well as the number of glutamyl units associated with these modifications using mass spectrometric analysis (MALDI & MS/MS). The modification at the CTAD (C-terminal acidic tail domain) could compensate for the lesser amount of acidic amino acid in dNAP1 and may account for the gain in nucleosome dissociation function. The second polyglutamylation site is located at the NLS (Nuclear Localization Sequence) (based on the conserved core domain of yNAP1 and dNAP1).
Keywords: chromatin; nucleosome assembly protein 1; polyglutamylation; molecular biology